Comunicación intercultural y su influencia en la calidad de vida en los habitantes de la Parroquia Borbón, cantón Eloy Alfaro de la Provincia de Esmeraldas, año 2021 - Caicedo Salazar, Josselyn Emerita (2021)
Intercultural communication is the interaction of information from two or more people of different cultures, this research work has as its main objective to determine the influence of intercultural communication on the quality of life of the inhabitants of the Borbón parish, Eloy Alfaro de In the province of Esmeraldas, it seeks to identify the types of intercultural communication, the advantages and disadvantages that affect intercultural communication, and the participation of the media in the development of cultural diversity and the contribution made by the importance of intercultural communication in the quality of life of individuals. The methodology used in this research starts from the deductive method to find the findings of the case from the general to the particular and continues with the inductive method to reach the conclusions of the information from the particular to the general; complementing the content analysis with descriptive and bibliographic research for the application of a structured virtual survey where the sample was 54 people with a population of 63 participants from the Bourbon parish. The main findings found showed that the beneficiaries had a positive attitude in relation to their knowledge of intercultural communication and the influence on their quality of life. Therefore, it is concluded that it is necessary to promote intercultural communication programs that help to strengthen and preserve the customs and traditions of the peoples.